Lost trail : nine days alone in the wilderness - Fendler, Donn, 1926-2016 (Down East Books : Distributed .. by National Book Network, 2011)
A twelve-year-old describes his nine-day struggles to survive after being separated from his companions in the mountains of Maine in 1939.